Manipulating transverse waves through 1D metamaterial by longitudinal vibrations. (15th February 2020) - Qian, Ying-Jing; Cui, Qing-Dian; Yang, Xiao-Dong; Zhang, Wei
Highlights: Transverse waves can be manipulated by longitudinal vibrations. Longitudinal frequency alters band structures by providing pseudo-stiffness. The longitudinal vibration mainly effects band gaps due to local resonance. Abstract: The idea of manipulating transverse waves by longitudinal vibrations has been proposed in this article. The band structures of distributed resonators on an Euler beam undergoing high frequency longitudinal vibrations have been investigated. The supplement of longitudinal vibration alters the transverse wave band structures by providing pseudo-stiffness. The varying band gaps of both Bragg scattering and local resonance have been studied focusing on the contribution of the longitudinal vibration. The analytical results are validated by the finite element numerical method. Graphical abstract: Image, graphical abstract